Going Native? Yes, If Allowed by Cross-Linguistic Similarity - Martínez de la Hidalga, Gillen; Zawiszewski, Adam; Laka, Itziar (Frontiers in Psychology, 2021)
Can native competence be achieved in a second language? Here, we focus on the Language Distance Hypothesis (Zawiszewski & Laka, 2020) that claims that early and proficient bilinguals can achieve native competence for grammatical properties shared by their two languages, whereas unshared grammatical properties pose a challenge for native-like syntactic processing. We present a novel behavioral and ERP study where early and proficient bilinguals behave native-like in their second language when processing (a) argument structure alternations in intransitive sentences involving agent versus patient subjects and (b) subject verb agreement, both of which are grammatical properties shared by their two languages of these bilinguals. Compared to native Basque bilinguals (L2Spanish) on the same tasks (Martinez de la Hidalga et al., 2019), non-natives elicited similar sentence processing measures: (a) in the acceptability task they reacted faster and more accurately to unaccusative sentences than to unergatives and to person than number violations: (b) they generated a larger P600 for agreement violations in unaccusative sentences than unergatives; (c) they generated larger negativity and positivity effects for person than for number violations. Previous studies on Basque-Spanish bilinguals find that early and proficient non-natives display effects distinct from natives in both languages when processing grammatical properties where Basque and Spanish diverge, such as argument alignment (ergative/nominative) or word order type (OV/VO), but they perform native-like for shared properties such as subject agreement and word meaning (Zawiszewski et al., 2011; Erdocia et al., 2014; de la Cruz-Pavía et al., 2015; Díaz et al., 2016; Erdocia & Laka, 2018; Zawiszewski & Laka, 2020; We contend that language distance, that is, the degree of similarity of the languages of the bilingual (Gamallo et al., 2017) is a crucial factor that deserves further and detailed attention to advance our understanding of when and how bilinguals can go native in a second language.